Establishment of a Transformation Coupled in vitro End Joining Assay to Estimate Radiosensitivity in Tumor Cells - Degenhardt, Sarah; Dreffke, Kristin; Schötz, Urlike; Petersen, Cordula; Engenhart-Cabillic, Rita; Rothkamm, Kai; Dahm-Daphi, Jochen; Dikomey, Ekkehard; Mansour, Wael Yassin (Frontiers in Oncology, 2020)
Here, we present a modified in vitro end-joining (EJ) assay to quantify EJ capacity, accuracy as well as pathway switch to alternative end-joining (Alt-EJ) or single strand annealing (SSA). A novel transformation assay was established to specifically measure circular repair products, which correlate with classical EJ efficiency. The EJ assay was validated using EJ-deficient mammalian cell lines (Ku80, DNA-PKcs, LigIV, or XRCC4 mutants). A pathway switch to Alt-EJ and SSA was seen exclusively in Ku-deficient cells. Circular EJ product formation correlated with cell survival and DSB repair capacity after X-irradiation. Investigation of 14 HNSCC cell lines revealed differences in the total EJ capacity but a broader variation in the amount of circular repair products. Sequencing of repair junctions in HNSCC cells demonstrated a predominance of high-fidelity EJ and an avoidance of both Alt-EJ and SSA. A significant correlation was observed between the amount of circular repair products, repair of IR-induced DSB and radiosensitivity. Collectively, these data indicate that the presented in vitro-EJ-assay can not only estimate the repair capacity of cancer cells to enable the stratification into radiosensitive or radioresistant, but can also identify repair pathway deregulation such as a switch to Alt-EJ or SSA, which enables tumor targeting.